2018
DOI: 10.1016/j.wasman.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Inside the small-scale composting of kitchen and garden wastes: Thermal performance and stratification effect in vertical compost bins

Abstract: Decentralized composting has been proposed as a best available practice, with a highly positive impact on municipal solid wastes management plans. However, in cold climates, decentralized small-scale composting performance to reach thermophilic temperatures (required for the product sanitization) could be poor, due to a lack of critical mass to retain heat. In addition, in these systems the composting process is usually disturbed when new portions of fresh organic waste are combined with previous batches. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 33 publications
1
32
2
Order By: Relevance
“…The main advantages of decentralized composting over centralized systems are summarized in Table 1. In a broad perspective, decentralized composting can help to decrease the cost and effort for transportation of waste for processing and treatment, and further reduce the need to construct new disposal facilities, enable local reuse of organic matter, create local small-scale enterprises as well as reduce costs associated with commercial fertilizer purchase [19,53,54]. Furthermore, the final compost product is comparatively of higher quality due to efficient separation and less intercontamination of wastes [55,56].…”
Section: General Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantages of decentralized composting over centralized systems are summarized in Table 1. In a broad perspective, decentralized composting can help to decrease the cost and effort for transportation of waste for processing and treatment, and further reduce the need to construct new disposal facilities, enable local reuse of organic matter, create local small-scale enterprises as well as reduce costs associated with commercial fertilizer purchase [19,53,54]. Furthermore, the final compost product is comparatively of higher quality due to efficient separation and less intercontamination of wastes [55,56].…”
Section: General Overviewmentioning
confidence: 99%
“…Community composting reactors can be different, in other words, "simpler", than centralized composters. Plastic bins in any shapes (i.e., rectangular, cylindrical, conical) are often used for community composting reactors [7,54]. Plastic drum reactors were also recently reported [59].…”
Section: Community Composting In the Operative Environmentmentioning
confidence: 99%
“…The temperature variation in the composting process Figure 2 didn't occur as described in the literature, where it shows that in the first stage, the temperature is around 40ºC, then in the second phase, thermophilic, it acts between 65º-70ºC and final stage of maturation, the temperature gradually decreases. This may have been influenced by the proportions of the residues, since even in winter (May to October), when the temperature ranged from 8 to 33 °C Figure 3, Arrigoni, et al [18] in Argentina, where the average annual temperature is 8.4 °C, performed a work with composting and the temperature of the process varied according to the literature. Several authors have observed different behavior of temperature in the composting process, this indicates that average values of temperature should not be considered as standard [19]; [20]; [21]; [22]; [23]; [24].…”
Section: Resultsmentioning
confidence: 99%
“…The process of composting can be used for different types of wastes such as on animal manures [25], food wastes [27], kitchen and garden wastes [28], sewage sludge [29], household organic waste [30] etc. However, studies shown some different methods of composting previously.…”
Section: Co-compostingmentioning
confidence: 99%